Two-loop mixed QCD-EW corrections to neutral current Drell-Yan - Tommaso Armadillo; Roberto Bonciani; Simone Devoto; Narayan Rana; Alessandro Vicini (Journal of High Energy Physics, 2022)
Abstract We present the two-loop mixed strong-electroweak virtual corrections to the neutral current Drell-Yan process and we provide, as supplementary material, the explicit formulae of the infrared-subtracted finite remainder. The final state collinear singularities are regularised by the lepton mass. The evaluation of all the relevant Feynman integrals, including those with up to two internal massive lines, has been worked out relying on analytical and semi-analytical techniques, in the case of complex-valued masses.